2017
DOI: 10.1111/ger.12296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yogurt fermented withLactobacillus delbrueckiissp. bulgaricusOLL1073R‐1 on the IgA flow rate of saliva in elderly persons residing in a nursing home: A before‐after non‐randomised intervention study

Abstract: Continuous intake of yogurt fermented with L. bulgaricus OLL1073R-1 may help improve the mucosal immune function in elderly people with weakened immune systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the same category of patients, L. delbrueckii subsp. bulgaricus OLL1073R-1 fermented milk was shown to increase the concentration of saliva IgA [144,145]. It moreover reduced the risk of infection in the elderly, increasing NK cell activity as well as enhancing the quality of life score [74].…”
Section: What Clinical Studies Saymentioning
confidence: 99%
“…In the same category of patients, L. delbrueckii subsp. bulgaricus OLL1073R-1 fermented milk was shown to increase the concentration of saliva IgA [144,145]. It moreover reduced the risk of infection in the elderly, increasing NK cell activity as well as enhancing the quality of life score [74].…”
Section: What Clinical Studies Saymentioning
confidence: 99%
“…Lactobacillus delbrueckii subsp. bulgaricus OLL1073R-1, a polysaccharide-producing lactic acid bacterial strain, has proven beneficial health effects on older people by preventing infection with influenza A virus subtype H3N2 via increasing the production of H3N2bound salivary IgA [68] and improving the mucosal immune function in elderly people with weakened immune systems [69]. The study by Makino and co-authors [39], which was among the investigated studies in this review and was additionally found in the reference list of included studies [38,53,54], also used this probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits marked immunemodulatory effects, such as the activation of biological defense mechanisms and natural killer cell activation, through induction of IFN-γ in mice (Makino et al, 2006(Makino et al, , 2010(Makino et al, , 2016. Furthermore, it was reported recently that L. bulgaricus OLL1073R-1 YC increased IgA secretion in saliva in elderly individuals and protected against invasion by foreign antigens and pathogens through the oral mucosa (Yamamoto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%